ANALISIS MARGIN TATANIAGA KARET(HEVEA BRASILIENSIS)KECAMATAN SALAM BABARIS KABUPATEN TAPINPROVINSI KALIMANTAN SELATAN (Analysis Marketing Margin of Crumb Rubber in Salam Babaris District of Tapin Regency of Kalimantan South Province) - Husinsyah -; Syahdi Rasyid (SEKOLAH TINGGI ILMU EKONOMI NASIONAL (STIENAS) BANJARMASIN, 2016)
Abstract, This research aims to determine the cost, margin, profit share and rubber trading system in the District Salam Babaris, Tapin district. The research was conducted from June to August 2016 in the District Salam Babaris Tapin district. Sampling is done by: (1) simple random method for farmers and (2) the snowball method for merchants. Analysis of the data using the formula and share margin trading system. The result showed that margin, share and profits derived rubber business administration institutions in the District Salam Babaris, Tapin District there are differences based trading system channel path. Recommended channels untu shorten trading system that is too long in the hope of obtaining a high share, smaller business administration costs and gain greater business administration.